A study on recruitment, selection, training and development and critical challenges of Aarong- BRAC social enterprise - Moushumi, Naznin Akhter (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.